Macromolecular syntheses during biosynthesis of prodigiosin by Serratia marcescens. - Williams, R P (1976)
Amino acids that were utilized as sole sources of carbon and nitrogen for growth of Serratia marcescens Nima resulted in biosynthesis of prodigiosin in non-proliferating bacteria. Addition of alanine, proline, or histidine to non-proliferating cells incubated at 27 C increased the rate of protein synthesis and also caused biosynthesis of prodigiosin. No increase in the rate of protein synthesis was observed upon the addition of amino acids that did not stimulate prodigiosin biosynthesis. Increased rates of synthesis of ribonucleic acid (RNA) and of deoxyribonucleic acid (DNA) (a small amount) also occurred after addition of amino acids that resulted in biosynthesis of prodigiosin. After incubation of 24 h, the total amount of protein in suspensions of bacteria to which alanine or proline was added increased 67 and 98%, respectively. Total amounts of DNA and of RNA also increased before synthesis of prodigiosin. The amounts of these macromolecules did not increase after addition of amino acids that did not induce biosynthesis of progidiosin. However, macromolecular synthesis was not related only to prodigiosin biosynthesis because the rates of DNA, RNA, and protein synthesis also increased in suspensions of bacteria incubated with proline at 39 C, at which temperature no prodigiosin was synthesized. The quantities of DNA, RNA, and protein synthesized were lower in non-proliferating cells than in growing cells. The data indicated that amino acids causing biosynthesis of prodigiosin in non-proliferating cells must be metabolized and serve as sources of carbon and of nitrogen for synthesis of macromolecules and intermediates. Prodigiosin was synthesized secondarily to these primary metabolic events.